Media arts : Arts education for a digital age - Peppler, Kylie A. (Teachers College RecordTeachers College Record, 2010)
The researcher draws upon over three years of extensive field study at a Computer Clubhouse (media arts studio) in south Los Angeles where underprivileged youth ranging in age from eight to 18 have access to programming environments utilizing graphic, music, and video production software. Using a mixed-methods design including interviews with young artists at the Clubhouse, video footage of Clubhouse youth in the process of art making, and an archive of youth media art projects, the researcher documents what youth learn through media arts making in informal settings. She also describes the implications for leveraging learning in a media arts context for learning in other academic content areas.
Keywords: création; enseignement; jeunesse